La incompletud y la busqueda del amor : entre la enfermedad mental y la aceptación personal (2020)
This auto-ethnography has the objective of analyzing the implications of psychiatric diagnosis and their follow-up treatments on patient's lives. To do so, it deepens into the memoirs and the personal, intimate life history of Maria Luisa, a patient diagnosed with borderline personality disorder and moderate depression, with the purpose of understanding the perception that she has of her self and how this diagnosis has impacted, both positively or negatively, her day-to-day life. Through this paper I present the history of Maria Luisa, her nine years of psychiatric treatment, her clinical story, her journals and the contextualization of that life onto the psychiatric practice and how it could relieve an emotional issue. To sum up, this research tries to focus on the patient's voice to try to acknowledge the complexity that hides behind the triad of diagnosis, treatments and hospitalizations.